2021
DOI: 10.1007/s42235-021-0065-4
|View full text |Cite
|
Sign up to set email alerts
|

Review of Recent Progress in Robotic Knee Prosthesis Related Techniques: Structure, Actuation and Control

Abstract: As the essential technology of human-robotics interactive wearable devices, the robotic knee prosthesis can provide above-knee amputations with functional knee compensations to realize their physical and psychological social regression. With the development of mechanical and mechatronic science and technology, the fully active knee prosthesis that can provide subjects with actuating torques has demonstrated a better wearing performance in slope walking and stair ascent when compared with the passive and the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…The new HDP utilizes a four-bar structure instead of the conventional single-axis knee joint. [28][29][30] The optimized fourbar structure of the knee joint restores the biological knee joint motion characteristics (Figure 4). Moreover, conventional prostheses in joint synergistic motion mainly rely on control techniques.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The new HDP utilizes a four-bar structure instead of the conventional single-axis knee joint. [28][29][30] The optimized fourbar structure of the knee joint restores the biological knee joint motion characteristics (Figure 4). Moreover, conventional prostheses in joint synergistic motion mainly rely on control techniques.…”
Section: Resultsmentioning
confidence: 96%
“…The optimized RCM structure matches the amputee's existing socket and is consistent with the dimensions of the rehabilitated leg. The new HDP utilizes a four‐bar structure instead of the conventional single‐axis knee joint 28–30 . The optimized four‐bar structure of the knee joint restores the biological knee joint motion characteristics (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…Active or powered prostheses have enhanced functionality in various conditions such as stair climbing (Sun et al, 2021), and have been shown to provide better functional and psychological outcomes compared to passive devices (Lathouwers et al, 2023). However, the higher functionality of active prostheses also increases the complexity of the system and the number of control parameters for tuning to personalize the prosthetic legs.…”
Section: Previous Research In Preferences For Lower-limb Prosthesis S...mentioning
confidence: 99%
“…One promising technology is robotic prosthetic legs that are motorized and intelligently controlled. Compared to passive alternatives that fail to replicate the behaviors of the healthy limb across various environments, robotic prostheses showed many potential advantages [2], including increased range of motion [3], enhanced stability and balance of wearers [4], [5], and ability to adapt to various terrains [6], [7].…”
Section: Introductionmentioning
confidence: 99%